Outcomes of Primary Tibiotalocalcaneal Nailing for Complicated Diabetic Ankle Fractures. (December 2019) - Ebaugh, M. Pierce; Umbel, Benjamin; Goss, David; Taylor, Benjamin C.
Background: Ankle fractures in patients with complicated diabetes have significantly increased the rates of complications and poorer functional outcomes when treated nonoperatively, and there have been only modest reductions when treated operatively. We hypothesized that the minimally invasive, robust construct that tibiotalocalcaneal fixation with an intramedullary nail offers would result in high rates of limb salvage, acceptable rates of complications, and less loss of function, in this difficult patient population. Methods: This was an institutional review board–approved retrospective study of 27 patients with complicated diabetes who underwent tibiotalocalcaneal nailing of their ankle fracture as a primary treatment without formal joint preparation. Patients with complicated diabetes were defined as having neuropathy, nephropathy, and/or peripheral vascular disease. The mean clinical follow-up was 888 days. Patients were screened for associated risk factors. Data were collected on surgical complications. The outcomes measured included length of hospital stay, loss of ambulatory level, amputation, and time to death. The mean age was 66 years with an average body mass index of 38 and hemoglobin A1c of 7.4. Six fractures were open. Results: The limb salvage rate was 96%. The average hospital stay was 6 days, and the mean time to weightbearing was 6.7 weeks. The fracture union rate was 88%. The surgical complication rate was 18.5%, with no instances of malunions, symptomatic nonunions, or Charcot arthropathy. Eight patients died by final follow-up (mean, 1048 days). An ambulatory level was maintained in 81% of the patients. Conclusion: With high limb salvage rates, relatively early weightbearing, maintained ambulatory level, and acceptable complication rates, we believe our technique can be considered an appropriate approach to increase the overall survivability of threatened limbs and lives in this patient population. Level of Evidence: Level IV, retrospective case series.